Maria Stehle and Beverly Weber. Precarious Intimacies: The Politics of Touch in Contemporary Western European Cinema. Northwestern UP, 2020. - Paul Ardoin (Studies in 20th & 21st Century Literature, 2021)
Review of Maria Stehle and Beverly Weber. Precarious Intimacies: The Politics of Touch in Contemporary Western European Cinema. Northwestern UP, 2020. 197 pp.
Keywords: precarious intimacies; Maria Stehle; Beverly Weber; affect; postcolonialism; Western European film